Small-scale model for investigating tunnel lining deformations. (September 2017) - Standing, J.R.; Lau, C.
Abstract: Tunnel linings in situ are rarely truly circular in form. Shapes depend on factors such as the nature of the lining, method of build, connections between segments, self-weight deformations and ground stresses. A small-scale two-dimensional simplified tunnel lining model comprising six segments was developed where the lining was loaded using a reaction ring. The results provide insight into factors that control the lining response: e.g. the deformed shape depends on the nature of the imposed loading, tightness of the bolts, number of segments and joint flexibility. This small-scale model was developed as a precursor to a sophisticated large-scale structural model used to assess the effect of tunnelling on existing tunnels (Yu et al., 2017). In this respect it proved very instructive, especially for assessing the method of loading the ring. An important message from the paper is how an inexpensive, but carefully thought out, small-scale model can provide great insight to the development of large-scale models that will involve orders of magnitude more time and expense. Many of the findings from the small-scale study were verified by the more realistic large-scale model which was able to provide details on deformations and stress changes in the segments and bolts.